2001
DOI: 10.3233/ies-2001-0075
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic and isometric shoulder rotation strength in the protracted position: A reliability study

Abstract: Scapular position has been hypothesized to influence rotator cuff function, but no current methods exist to reliably measure shoulder rotation strength in different scapular positions. The purpose of this study was to develop a reliable technique to measure isokinetic (ISOK) and isometric (ISOM) shoulder rotation strength with the scapula protracted. Ten healthy volunteers (5 male, 5 female, ages 20-41) completed two to three ISOM and five ISOK (90 degrees/second) internal rotation (IR) and external rotation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Eleven studies reported ICC but without 95% CI. 21,26,28,30,31,33,34,[36][37][38][39] Of the strata examined, 28 of 30 showed at least 75% of the ICC results !0.70 and the overall rating of the results was "sufficient." The IR con at 90 /s revealed 66% of the results !0.70, and the ER con /IR con ratio at 120 /s revealed 50% of the results !0.70; these strata were rated as "indeterminate" (see table 3).…”
Section: Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies reported ICC but without 95% CI. 21,26,28,30,31,33,34,[36][37][38][39] Of the strata examined, 28 of 30 showed at least 75% of the ICC results !0.70 and the overall rating of the results was "sufficient." The IR con at 90 /s revealed 66% of the results !0.70, and the ER con /IR con ratio at 120 /s revealed 50% of the results !0.70; these strata were rated as "indeterminate" (see table 3).…”
Section: Reliabilitymentioning
confidence: 99%
“…All 21 studies evaluated reliability in a test-retest design. 6,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] We present the summarized results, the overall rating of the results, and the quality of evidence in the summary of findings table (table 3). Most studies reported the ICC, but 5 studies used Pearson correlation coefficient, variability, or coefficient of variation.…”
Section: Reliabilitymentioning
confidence: 99%
“…The reproducibility and the reliability of isokinetic shoulder assessment has been investigated in several studies (Nitschke, 1992;Mayer et al, 1994a,b;Burnham et al, 1995;Durall et al, 2000;Mandalidis et al, 2001c;Smith et al, 2001;van Meeteren et al, 2002;Forthomme et al, 2003a,b;Hill et al, 2005;Kakebeeke et al, 2005). Mandalidis et al (2001c) observed moderate to high ICC values (0AE76 -0AE93) for all measured variables when assessed shoulder rotators in the scapular plane.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the exercise performance of the shoulder joint rotator cuff before and after training, the average powers of the shoulder internal and external rotation motions were measured with a Biodex System 3 isokinetic dynamometer (Biodex Medical Systems, Shirley, New York, USA) on a scapular plane 14 , 15 , 16 , 17 , 18 ) . The one-way ANOVA test was used to compare average power progresses between the two groups.…”
Section: Methodsmentioning
confidence: 99%